Photocatalysis and Bandgap Engineering Using ZnO Nanocomposites - Muhammad Ali Johar; Rana Arslan Afzal; Abdulrahman Ali Alazba; Umair Manzoor (Advances in Materials Science and Engineering)
Nanocomposites have a great potential to work as efficient, multifunctional materials for energy conversion and photoelectrochemical reactions. Nanocomposites may reveal more improved photocatalysis by implying the improvements of their electronic and structural properties than pure photocatalyst. This paper presents the recent work carried out on photoelectrochemical reactions using the composite materials of ZnO with CdS, ZnO with SnO2, ZnO with TiO2, ZnO with Ag2S, and ZnO with graphene and graphene oxide. The photocatalytic efficiency mainly depends upon the light harvesting span of a material, lifetime of photogenerated electron-hole pair, and reactive sites available in the photocatalyst. We reviewed the UV-Vis absorption spectrum of nanocomposite and photodegradation reported by the same material and how photodegradation depends upon the factors described above. Finally the improvement in the absorption band edge of nanocomposite material is discussed.